The Preservation of Ratib Saman in Palembang, 2000-2019 - Indah Pratiwi; Sakinah Sakinah; Syarifuddin Syarifuddin; Supriyanto Supriyanto (IHiS (Indonesian Historical Studies))
Ratib Saman is the most important dhikr that contains invocation. Ratib Saman was first introduced by Shaykh Abdul Samad al-Palimbani and was part of the teachings of the Sammaniyah order. The practice of Ratib Saman in Palembang had shifted because there were too few followers who read the Ratib Saman. However, over time, the Ratib Saman tradition began to be preserved by the people of Palembang, especially in old mosques. Ratib Saman is routinely practiced on twice a week. This research aims at determining the beginning of the practice of Ratib Saman in Palembang and the preservation of Ratib Saman in Palembang that are still being held. The historical method used to get factual explanations on the origin of Ratib Saman. The data collection was conducted by observation, documentation, and interview. In addition, the Ratib Saman tradition is also widely practiced by their selves on special occasions. Ratib Saman readings are attended either by young or old people. It had become a tradition of the people of Palembang, which can be seen from the practice of Ratib Saman that was held regularly and whose reading had a characteristic. Therefore, it should be preserved so that it does not get erased by time.